Identifying Crystal Accumulation in Granitoids through Amphibole Composition and In Situ Zircon O Isotopes in North Qilian Orogen. (27th November 2021) - Chen, Shuo; Niu, Yaoling; Wang, Xiaohong; Xue, Qiqi; Sun, Wenli
Abstract: Granitoids are the main constituents of the continental crust, and an understanding of their petrogenesis is key to the origin and evolution of continents. Whether crystal fractionation is the dominant way to generate evolved magmas has long been debated, mostly because such processes would produce large volumes of complementary cumulates, which remains elusive. Mafic magmatic enclaves (MMEs) are ubiquitous in granitoids and their presence was initially recognized as cumulates. However, because many MMEs lack obvious evidence of accumulation, such as the classic cumulate textures and modal layering, the cumulate origin of MMEs has been abandoned and the model of magma mixing between mafic and felsic magmas has become popular. In this study, we conduct a combined study of amphibole composition and in situ O isotopes in zircons on three suites of orogenic granitoids with MMEs from the North Qilian Orogenic Belt (NQOB). We find that the MMEs and their host granodiorites show overlapping zircon δ 18 O values, affirming that they share the same parental magmas. The amphibole compositions indicate that amphiboles from the MMEs are not in equilibrium with a melt whose composition was that of the bulk-rock. These new data, together with the published bulk-rock data, suggest that the MMEs in our study have clear cumulate signatures and are thus of cumulate origin. Our study provides evidence for crystal accumulation in granitoids in the NQOB. This new understanding calls for re-examination on the petrogenesis of some intermediate magmatic rocks (granitoid/andesite) in discussing models of continental crustal growth.